KERUSAKAN PERUMAHAN PERUMNAS DAN KPR-BTN DI TIPE TANAH ALUVIAL DAN REGOSOL OLER ORGANISME PERUSAK KAYU - Ginuk Sumarni; Agus Ismanto (Jurnal Penelitian Hasil Hutan, 1991)
This  paper  deals  with  a descriptive   account   on  the  infestation   of  wood  destroying   organisms  on PERUMNAS    and KPR-BTN   houses  on  the  alluvial and  regosol  soil  types, Data  were  collected   through  interviews  and questionaires.Results  of  the  investigation  reveal  that  the  untreated  red meranti  wood group  was severely  attacked  by  termites  and fungi  after 7 years old.  Mean  while,  the  treated  wood  was also attacked   by  fungi  after  14 years old.  Untreated  kamper  wood   was attacked   by  fungi  after  5 years  old.  whereas  the  untreated.  keruing  wood  was attacked   by  termites  and fungi  after  11 years  old.